Selection of arbuscular mycorrhizal fungi for the forage peanut intercropped with signal grass - Miranda, Elias Melo de; Júnior, Orivaldo José Saggin; Silva, Eliane Maria Ribeiro da (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate and select efficient arbuscular mycorrhizal fungi (AMF) to promote growth of the intercropped Arachis pintoi and Brachiaria decumbens, in the presence and absence of competing autochthonous AMF. The experiment was performed under greenhouse conditions at Embrapa Agrobiologia, in Seropédica, RJ. The experimental design was completely randomized with three repetitions, in a 2x6 factorial arrangement, with two substrates (non sterile and sterile) derivative of a Fragiudult (Planosol)and six treatments of inoculation (Acaulospora morrowiae, Entrophospora Colombiana, Gigaspora margarita, Glomus clarum, Scutellospora heterogama, and a noninoculated control); besides a monoculture of each forage as a reference control. Three cuts were made during the experimental period, at different intervals, until the competition and substrate depletion made the permanence of the leguminous unviable in the consortium. Benefits were observed for AMF inoculation to the production of A. pintoi dry matter, being G. clarum themore efficient species. The use of seedlings efficiently colonized by AMF facilitates the establishment and initial growth of forage peanuts plants, increasing their competitive capacity with Brachiaria.
Keywords: Arachis pintoi; Brachiaria decumbens; mixed pastures